2014
DOI: 10.1128/jcm.00899-14
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Acute Nongonococcal Urethritis in Men Differ by Sexual Preference

Abstract: N ucleic acid amplification techniques (NAAT) have allowed greater understanding of the variety of pathogens involved in acute nongonococcal urethritis (NGU) (1). This has included the recent recognition of Mycoplasma genitalium, herpes simplex virus (HSV), and adenoviruses as urethral pathogens (2-5), although in a significant proportion of cases no urethral pathogen is currently identified. The role of Ureaplasma urealyticum in NGU has been somewhat controversial, but recent evidence implicates specific biov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Mycoplasma genitalium has emerged as the second most common aetiological agent, causing 10–30 % of cases [ 5 7 ], with a double infection with C. trachomatis in 5 to 15 % [ 8 ]. In 30–60 % of the cases with NGU neither C. trachomatis nor M. genitalium is detected [ 9 , 10 ]. Pathogen negative NGU is more likely with increasing age, the absence of discharge or clinical symptoms, and engagement in low-risk practices [ 9 11 ].…”
Section: Aetiologymentioning
confidence: 99%
“…Mycoplasma genitalium has emerged as the second most common aetiological agent, causing 10–30 % of cases [ 5 7 ], with a double infection with C. trachomatis in 5 to 15 % [ 8 ]. In 30–60 % of the cases with NGU neither C. trachomatis nor M. genitalium is detected [ 9 , 10 ]. Pathogen negative NGU is more likely with increasing age, the absence of discharge or clinical symptoms, and engagement in low-risk practices [ 9 11 ].…”
Section: Aetiologymentioning
confidence: 99%
“…C. trachomatis was detected in 401 men (31%), and Mycoplasma genitalium was diagnosed in 134 men (10%). 12 A Japanese study involving 51 men showed that the 16S ribosomal RNA gene of Ureaplasma urealyticum (quantified by means of a real-time polymerase-chain-reaction [PCR] assay) was associated with the presence of symptoms of urethritis and higher leukocyte counts in first voided urine. 13 …”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%
“…Epididymo-orchitis [14,15,32,33] Acute gonococcal [34] / non-gonococcal urethritis (NGU) [35][36][37][38][39][40] / non specific urethritis (NSU), Chronic…”
Section: Clinical Vide-infra See Belowmentioning
confidence: 99%